Independent switching technique to remove abnormal output voltage in hybrid active NPC inverters - Song, Min Geun; Kim, Seok Min; Lee, Kyo Beum (Journal of Power Electronics, 2021)
This paper proposes the independent switching technique to remove abnormal output voltage in hybrid active neutral-point clamped (ANPC) inverters. The hybrid ANPC inverter is composed by mixing silicon (Si) devices and silicon carbide (SiC) devices, unlike the conventional ANPC inverter which is generally composed of Si devices only. SiC devices provide low switching losses under a high switching frequency and a high withstand ability under high temperature compared with Si devices. Therefore, the hybrid ANPC inverter using SiC devices provides low power losses, high efficiency, and high reliability compared with the conventional ANPC inverters. In this hybrid ANPC inverter, abnormal output voltages are generated when the sinusoidal output current crosses the zero point. The abnormal output voltages are momentary pulses that must not be generated, and these pulses distort the output current and degrade the power quality. These pulses have two typical causes: one is from the switching operation time difference between switches, and the other is from deadtime. This paper proposes the independent switching technique to remove the abnormal voltages caused by the two reasons and verifies the proposed technique by simulation and experiment.
Keywords: Active neutral point clamped; High reliability; High switching frequencies; High temperature; Silicon carbides (SiC); Sinusoidal output; Switching operations; Switching techniques; Abnormal output voltage; Hybrid active neutral-point clamped inverter; Independent switching; Silicon carbide devices; Three-level inverters